The effects of dental health education intervention of PTA members in improving the dental health of public elementary schoolchildren in West Jakarta. - Chandrasari, Winny
Based on the results of an evaluation survey of the School Dental Program in Jakarta done 1988, it was found out that the dental health of elementary school children in Jakarta is still below par in terms of the goals of School Dental Health Program (SDHP).